Developing an Early Warning System Based on Correlation Analysis For Dengue Haemorrhagic Fever - ., Sumiati; ., Hidayat; ., Suprono; ., Fachrudin; ., Satyaningsih (KnE Life Sciences, 2021)
Several cities in Indonesia have been declared as Dengue Haemorrhagic Fever (DHF)-endemic areas, including East Jakarta, an administrative city of DKI Jakarta Province. Surveillance is the most important activity in controlling and monitoring the development of DHF. This ecological study was conducted to assess the correlation between DHF cases, vector density (Larva Free Index [LFI]) and climate (rainfall and humidity). While the DHF cases were collected from hospitals report, vector density data were obtained from public health centres and climate data were obtained from the Meteorological, Climatological, and Geophysical Agency (BMKG). The correlations between DHF cases, vector density, and the climate were analysed based on weekly data, from week 1 to week 33 of 2019. This study showed a consistent trend of increasing and decreasing DHF cases with rainfall and LFI. DHF cases and LFI had a strong negative correlation (r = –0.72) at a time lag of six weeks. LFI and rainfall also showed a strong negative correlation (r = –0.86) at a time lag of five weeks. The strongest correlation between DHF cases and rainfall was found at week 8 (r = 0.87). Humidity, also an indicator of climate, had a strong positive correlation (r = 0.80) with DHF cases at the 11th-week time lag. However, contrarily, humidity had a strong negative correlation with LFI at the 5th-week time lag. These findings can be used for developing an early warning system that is reinforced by utilizing the application of HDF–climate information. Keywords: dengue fever, vector, climate, early warning system